Safeguarding the interests of future generations in the ECHR system: which perspectives arise from a new Protocol to the European Convention on Human Rights? (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
In 2021 the Parliamentary Assembly of the Council of Europe renewed its proposal to adopt an optional Protocol to the ECHR on the right to a safe, clean, healthy and sustainable environment. This proposal explicitly recalls future generations several times as an object of protection and as the holder of this right. Despite the interesting innovative aspects of the proposed text, the adoption of this Protocol would represent a challenge for the ECHR control system in relation to notions such as that of “potential or future victim” or “state jurisdiction”.
Keywords: Sustainable environment; ECHR draft protocol; future generations; climate justice; jurisdiction